2020
DOI: 10.1038/s41419-020-2471-7
|View full text |Cite
|
Sign up to set email alerts
|

Sepiapterin reductase promotes hepatocellular carcinoma progression via FoxO3a/Bim signaling in a nonenzymatic manner

Abstract: Sepiapterin reductase plays an enzymatic role in the biosynthesis of tetrahydrobiopterin, which is reported in limited studies to regulate the progression of several tumors. However, the role of sepiapterin reductase in hepatocellular carcinoma remains largely unknown. Here, we found that sepiapterin reductase was frequently highly expressed in human hepatocellular carcinoma, which was significantly associated with higher T stage, higher tumor node metastasis stage, and even shorter survival of hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Here, we identified 101 LUAD-specific enhancers linked to CENPA, FOXM1, and MYBL2 that show correlations with worse survival (Fig 7, S3B Table). For example, we found that the enhancer probe cg04161113, whose activation (low DNA methylation) is associated with poor survival, is potentially regulating the SPR gene, which was recently reported as an oncogene in liver cancer [40].…”
Section: Plos Geneticsmentioning
confidence: 86%
See 1 more Smart Citation
“…Here, we identified 101 LUAD-specific enhancers linked to CENPA, FOXM1, and MYBL2 that show correlations with worse survival (Fig 7, S3B Table). For example, we found that the enhancer probe cg04161113, whose activation (low DNA methylation) is associated with poor survival, is potentially regulating the SPR gene, which was recently reported as an oncogene in liver cancer [40].…”
Section: Plos Geneticsmentioning
confidence: 86%
“…SPR (sepiapterin reductase) is located~177kb upstream of the enhancer probe. A recent study showed that SPR depletion inhibited liver cancer cell proliferation and promoted cancer cell apoptosis in vivo [40], suggesting its role as an oncogene. Gene ontology (GO) analyses revealed that target genes potentially regulated by CENPA, FOXM1, and MYBL2 are involved in cell cycle, cellular response to DNA damage stimulus, chromosome organization, and DNA repair (S8A and S8B Table).…”
Section: Identification Of Cenpa/foxm1/mybl2-linked Enhancers Associamentioning
confidence: 99%
“…Additional reports from pre-clinical studies also indicated that FOXO3 upregulation is related to HCC oncogenicity via the overexpression of the long noncoding RNAs (lncRNAs) PRR34 antisense RNA 1 (PRR34-AS1) [ 17 ] and LOC554202 [ 30 ], or by the circular RNA circFBXO11/miR-605 axis [ 13 ]. Contrary to all the above-mentioned results, the article by Wu et al [ 31 ] described that reduction in FOXO3 nuclear translocation and activity could be involved in sepiapterin reductase-mediated HCC progression. Considering all the previous evidence, which mostly defends a tumor-promoting action of the positive regulation of FOXO3, our meta-analysis certainly supports the findings reported by the majority of studies and underscores the role of FOXO3 overexpression on fostering HCC development.…”
Section: Discussionmentioning
confidence: 78%
“…However, site‐directed mutagenesis of SPR indicates that mutation of Asp‐257 to histidine abolished sepiapterin reduction activity but had minimal effects on reactive oxygen species production, 43 suggesting the biological function of the non‐enzymatic activity of SPR (Table 1). Moreover, our published study indicated that SPR could promote hepatocellular carcinoma progression via FoxO3a/Bim signalling in a non‐enzymatic manner, while its enzymatic activity might have no effect on hepatocellular carcinoma development 44 . Overall, SPR plays a key role in different biological processes, and these effects might be related not only to its enzymatic activity but also to its non‐enzymatic function.…”
Section: Biological Functionsmentioning
confidence: 92%